Influence of presence of ammonium in the hydrothermal illitization of smectite - Bentabol-Manzanares, María José (Alberto López Galindo, 2017)
During diagenesis, several reactions induce changes both in phyllosilicates and organic matter, which in basins associated to the production of hydrocarbons leads to ammonium fixation in illite and micas [1] and to dissolution induced by organic acids [2] [3]. Dissolution processes may contribute to the smectite-to-illite transformation, stabilized by fixation of K (and NH4 +). Ammonium is a weak acid in solution. Under neutral conditions where the concentration of hydronium is very low (<10-7 M), ammonium contributes to smectite dissolution. The effect of organic acid on silicates dissolution is partially known, but the potential role of ammonium is completely novel.
Keywords: Filosilicatos; Amonio; Ammonium; illite; smectite; hydrothermal synthesis